Hessian fly associated microbes: dynamics, transmission and essentiality - Bansal, Raman (Kansas State University, 2010)
Keeping in view the important roles of bacteria in almost every aspect of insect’s life, the current study is the first systemic and intensive work on microbes associated with Hessian fly, a serious pest of wheat crop. A whole body analysis of Hessian fly larvae, pupae, or adults suggested that a remarkable diversity of bacteria is associated with different stages of the insect life cycle. The overriding detection of genera Acinetobacter and Enterobacter throughout the life cycle of Hessian fly suggested a stable and intimate relationship with the insect host. Adult Hessian flies have the most dissimilar bacterial composition from other stages with Bacillus as the most dominant genus. Analysis of 5778 high quality sequence reads obtained from larval gut estimated 187, 142, and 262 operational taxonomic units at 3% distance level from the 1st, 2nd, and 3rd instar respectively. Pseudomonas was the most dominant genus found in the gut of all three instars. The 3rd instar larval gut had the most diverse bacterial composition including genera Stenotrophomonas, Pantoea, Enterobacter, Ensifer, and Achromobacter. The transovarial transmission of major bacterial groups provided evidence of their intimate relationship with the Hessian fly. The Hessian fly is known to manipulate wheat plants to its own advantage. This study demonstrated that the combination of a decrease in carbon compounds and an increase in nitrogen compounds in the feeding tissues of Hessian fly-infested plants results in a C/N ratio of 17:1, nearly 2.5 times less than the C/N ratio (42:1) observed in control plants. We propose that bacteria associated with Hessian fly perform nitrogen fixation in the infested wheat, which was responsible for shifting the C/N ratio. The following findings made in the current study i.e. the presence of bacteria encoding nitrogenase (nifH) genes both in Hessian fly and infested wheat, exclusive expression of nifH in infested wheat, presence of diverse bacteria (including the nitrogen fixing genera) in the Hessian fly larvae, presence of similar bacterial microbiota in Hessian fly larvae and at the feeding site tissues in the infested wheat, and reduction in survival of Hessian fly larvae due to loss of bacteria are consistent with this hypothesis. The reduction in Hessian fly longevity after the loss of Alphaproteobacteria in first instar larvae, highest proportion of Alphaproteobacteria in insects surviving after the antibiotic treatments and the nitrogen fixation ability of associated Alphaproteobacteria strongly implies that Alphaproteobacteria are critical for the survival of Hessian fly larvae. This study provides a foundation for future studies to elucidate the role of associated microbes on Hessian fly virulence and biology. A better understanding of Hessian fly-microbe interactions may lead to new strategies to control this pest.
Keywords: Hessian Fly; Bacteria; Wheat; Microbiota; Symbiosis; Nitrogenase; Biology, Entomology (0353); Biology, Microbiology (0410); Biology, Molecular (0307)